Zinc portioning and allocation patterns among various tissues confers variations in Zn use efficiency and bioavailability in lentil genotypes - Rasheed, Naser; Maqsood, Muhammad Aamer; Aziz, Tariq; Ashraf, Muhammad Imran; Saleem, Ifra; Ehsan, Shabana; Nawaz, Allah; Bilal, Hafiz Muhammad; Xu, Minggang (Frontiers in Plant Science, 2024)
Zinc (Zn) is essential for plants and animals as it plays significant roles in several physiological and biological processes. Its deficiency in soil results in low Zn content food and is one of the major reasons of Zn malnutrition in human. Biofortification of crops with zinc (Zn) is a viable approach to combat this malnutrition, especially in developing countries. A hydroponic study was executed to study the response and Zn partitioning in various lentil genotypes. Eight preselected lentil genotypes (Line-11504, Mansehra-89, Masoor-2006, Masoor-85, Line-10502, Markaz-09, Masoor-2004 and Shiraz-96) were grown in solution culture with two Zn levels (control and adequate Zn). Plants were sown in polythene lined iron trays having two inches layer of prewashed riverbed sand. After 10 days of germination, seedlings were transplanted to 25L capacity container having nutrient’s solution for 15 days, and afterwards these plants were divided into two groups receiving either 2.0 μM Zn or no Zn levels. Three plants of each genotype were harvested at vegetative growth stage (60 DAT) and the remaining three at physiological maturity (117 DAT). Plants were partitioned into root, shoot and grains at harvest. Significant variations in root and shoot dry matter production, grain output, partitioning of Zn in plant parts (root, shoot and grain), grain phytate reduction and Zn bioavailability were observed among genotypes. The Zn efficient genotypes (Line-11504 and Mansehra-89) produced more root and shoot dry weights at both harvests. There were a positive correlation of relative growth rate of root with grain phytate concentration (r = 0.55) and [phytate]:[Zn] ratio (r = 0.67). Zn-efficient genotype Mansehra-89 had maximum root shoot ratio (0.57) and higher grain Zn (60 mg kg-1) with respective reduced grain phytate (17 µg g-1) and thus, had more Zn bioavailability (3.01 mg d-1). The genotypic ability for Zn uptake and accumulation within different plant tissues may be incorporated in future crop breeding for improving nutrition of undernourished consumers.